The trade-off between soil water recovery and nitrate leaching following the orchard-to-cropland conversion in the Chinese Loess Plateau - Hanyang Tian; Mingjuan Jin; Sidra Sohail; Chenchen Ma; Chenyun Bai; Jiangbo Qiao; Xiaoyang Han; Ming’an Shao (Scientific Reports)
Abstract A large-scale conversion of apple orchards into farmland has occurred in the tableland region of the Chinese Loess Plateau due to the aging of apple trees and the increase in pests and diseases. However, the impact of this conversion on soil desiccation recovery and soil nutrient transportation remains unclear, posing a new challenge for sustainable agricultural development in the region. The study employed the space-time substitution approach to select a long-standing orchard and croplands that has been growing maize for 1-, 3-, 5-, and 10-years post-orchard conversion as sampling sites, to investigate the effects of recovery durations of orchard-to-cropland conversion on deep soil water recharge and residual nitrate dynamics, as well as the key factors driving these changes. The results indicated that within 5 years, the conversion led to a rapid recharge of desiccated deep soil (6–9 m), followed by a stable and slow increase in subsequent years. The annual soil water recovery rate in the deep soil was as high as 5.90 mm m−1 a−1. While, the increased water input also caused rapid leaching and accumulation of nitrate in the deep soil, with its peak depth increasing significantly from 3.4 m to 7.0 m over time (R2 = 0.92). Soil water was identified as the key factor influencing nitrate leaching, with a correlation coefficient of 0.48 (P < 0.05). In conclusion, orchard-to-cropland conversion effectively replenished the deep soil water in the short term but also accelerated soil nitrate leaching. Therefore, while large-scale conversion of orchards to farmland is undertaken, it is crucial to acknowledge the trade-off relationship involving the recharge of deep soil water and the subsequent increase in deep nitrogen leaching. The findings of this study hold significant implication for the management of water and nutrient resources after the conversion of orchards to farmland, highlighting the necessity to mitigate nitrogen leaching while soil water is being restored.